Laccases production by A.blazei mushroom grown either in composted or non-composted substrates - Gonzalez Matute, Ramiro (2013)
Agaricus blazei is an edible and medicinal mushroom commonly cultivated on compost. However, non-composted substrates are being particularly studied for specialty mushrooms because their economic and labour advantages. Addition of salt minerals to the substrate or casing materials may stimulate both the synthesis and activity of enzymes involved in the mushroom substrate biotransformation and eventually lead to an increase not only in mushroom productivity but in the fruitbody mineral content too. Remaining substrates from mushroom cultivation are a potential source for the extraction of high valued ligninolytic enzymes like laccases. The main objective of this study was to determine the laccase activity level produced by A. blazei on different phases of its growth cycle, using composted and non-composted substrates. It was also studied the A. blazei laccase production in substrates, either in the presence or in the absence of Cu2+ or Zn2+ (100 or 200 ppm). Results showed that laccase activity depends on the substrate used and varies along the different phases of cultivation. It was also demonstrated, that laccase production and its subsequent accumulation in a substrate are not necessarily correlated with the mycelia growth rates and mushroom production yields. The incorporation of Cu2+ (100 and 200 ppm) solutions on top of the casing layer (composted substrate) or as part of the formula (noncomposted substrates), stimulated the laccase production in the studied substrates. In the case of Zn2+, only the addition of 100 ppm had a positive effect on laccases and mainly in composted substrates.